The Influence Of Hardskills &Softskills, Emotional Intelligence, Interpersonal Communication On Employee Performance - Fitriyanti; Fariha azzahra (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2023)
Background : Competition in the retail world is currently very tight due to the increasing number of competitors, so companies are required to improve the performance of human resources through skills and abilities, both hard skills and soft skills, to support the company's operations running well. Apart from that, improving employee performance also needs to be seen from the comfort of the work environment through Emotional Intelligence as the basic ability of employees to create comfort in the work environment. However, there are other factors that support performance, namely Interpersonal Communication.   Purpose: Based on the background and problem formulation explained, the aim of this research is to describe and analyze the influence of hard skills and soft skills on employee performance, describe and analyze the influence of emotional intelligence on employee performance, describe and analyze the influence of interpersonal communication on employee performance.   Methods: This research uses a quantitative approach which aims to test the hypothesis formulated. Determining the number of samples used the Slovin formula with a purposive sampling technique and obtained a sample of 95 respondents. Analyzed using the Partial Least Square (PLS) statistical analysis technique.   Conclusion: So, Hardskills and Softskills, Emotional Intelligence play a role in improving employee performance.   Suggestion: This research is a theory development, so the future agenda is to develop the research model by expanding to a more complex analysis